2022
DOI: 10.1111/echo.15404
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study of carotid variables under ultrasound analysis as predictors for the risk of coronary arterial atherosclerosis

Abstract: Background: Carotid atherosclerosis by ultrasound scanning can be considered as an ideal window to reflect systemic artery atherosclerosis, which has aroused wide concern for predicting the severity of coronary artery atherosclerosis clinically. Ultrasound radio frequency (RF) data technology has enabled us to evaluate the carotid structure and elastic function precisely, for predicting the severity of coronary artery atherosclerosis.Methods: Patients with suspected coronary artery disease (CAD) underwent coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…However, it is an invasive method with associated risks. Some studies have suggested that the carotid intima-media thickness (CIMT) serves as a rapid and reproducible marker for CAD [ 2 , 3 ]. Tarnoki et al [ 4 ] demonstrated the genetic influence on CIMT in a longitudinal twin study.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is an invasive method with associated risks. Some studies have suggested that the carotid intima-media thickness (CIMT) serves as a rapid and reproducible marker for CAD [ 2 , 3 ]. Tarnoki et al [ 4 ] demonstrated the genetic influence on CIMT in a longitudinal twin study.…”
Section: Introductionmentioning
confidence: 99%